Turnover intention of foreign trained physicians in German rehabilitation facilities-a quantitative study - Eva Jansen; Johanna Schmidt; Manuela Marquardt (BMC, 2024)
Abstract Background Germany's medical specialist shortage is an acute challenge, especially in the rehabilitation segment. One countermeasure is to recruit foreign trained physicians (FTP), but the high turnover of FTP is a burden on the departments that train them and integrate them professionally. Preliminary research showed that currently one in three physician positions in German Pension Insurance (DRV) contract facilities is filled by FTP.This paper examines factors related to turnover intention of FTP in German rehabilitative departments. Methodology In spring 2022, we surveyed FTP across all inpatient and outpatient rehabilitation departments under the German Pension Insurance, using a two-stage cross-sectional approach. We conducted an online survey of FTP and developed a specialized questionnaire that captured sociodemographic, occupation related and professional biographical data, turnover intention, satisfaction, difficulties with professional integration and departmental structural characteristics. To analyze retention within the rehabilitation field, we used a measure of turnover intention, taking into account the direction of potential turnover, residency requirements and considerations of returning to the rehabilitation field. The data was evaluated in a subgroup analysis comparing FTP with and without turnover intention using Fisher's exact tests. Results The sample includes n = 145 FTP, 119 stating no turnover intention and 27 with turnover intention. More than half of FTP with turnover intention wished to move to an acute care hospital. FTP with turnover intention are comparatively younger and came to Germany and were employed in the rehabilitation departments more recently, indicating an earlier career stage. Besides, career-related and regional factors show the strongest relation to turnover intention. Discussion and conclusion The results reveal a group of "established FTP" whose professional integration has been successfully completed. FTP with turnover intention are comparatively younger, career-oriented physicians for whom work in a rehabilitative facility is a career springboard to gain a foothold in acute care clinics. A limitation is that FTP with turnover intention are difficult to reach and may be underrepresented in our sample.